MEKANISASI BUDIDAYA JAMUR TIRAM PUTIH UNTUK MENINGKATKAN KAPASITAS PRODUKSI PETANI - Made Rasta; Putu Wijaya Sunu; I Wayan Adi Subagia; I K Widana (P3M Politeknik Negeri Bali, 2018)
Mushrooms are one type of food that needs attention regarding community food security. White oyster mushroom (Pleurotus ostreatus) is currently quite popular and much loved by the public because of its delicious taste and high nutritional value. Aside from being a food ingredient, oyster mushrooms are also useful as health or medicine. White oyster mushroom cultivation is one of the agribusiness businesses that have a large business opportunity because it has an increasing economic value. Pleurotus ostreatus is known as a fungus that is easily cultivated and is widely developed on wood substrate media that has been packaged in plastic bags and then incubated and maintained in a contact house. On the other hand, the presence of mushroom commodities in the market is still scarce, the scarcity of mushrooms due to the lack of mushroom cultivation producers and the activity of mushroom production is not optimal. Partner problems are an understanding of innovation and technology that supports and can help ease the work of mushroom cultivation to increase production is still limited. The aim to be realized from this activity is to strengthen and increase the capacity of innovation and technology in mushroom cultivation so that the productivity and economy of mushroom farmers can be increased. In order to overcome these obstacles an automatic temperature and humidity regulation system, baglog press machine and training on machine operation and marketing management are carried out. The results of the Community Partnership Program (PKM) activities are the availability of mushroom house temperature and humidity control machines, baglog press machines. So that is expected to increase production and have an impact on the economy of mushroom farmers that are getting better.